1999
DOI: 10.1046/j.1365-2249.1999.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of CTLA-4 (CD152) on CD4+ T cells in HIV infection

Abstract: SUMMARYCTLA-4 (CD152) is a surface molecule of activated T cells with sequence homology to CD28. Both molecules bind to the same ligands, B7.1 (CD80) and B7.2 (CD86) but have antagonistic functions. While CD28 is an important costimulator, CTLA-4 has an essential inhibitory function in maintaining the homeostasis of the immune system. Down-regulation of CD28 predominantly on CD8þ T cells has been described in HIV infection, but analysis of CTLA-4 is complicated by its low expression levels. Here we have used p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 45 publications
6
42
0
Order By: Relevance
“…Cell surface expression of CTLA-4 increases during HIV protein production (ref. 31 and supporting information), suggesting that CTLA-4-containing granules are apparently signaled to translocate to the plasma membrane at some late stage of HIV virus assembly. Because of their shared residence in granules, CTLA-4 and Env are recruited concomitantly to the cell surface (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Cell surface expression of CTLA-4 increases during HIV protein production (ref. 31 and supporting information), suggesting that CTLA-4-containing granules are apparently signaled to translocate to the plasma membrane at some late stage of HIV virus assembly. Because of their shared residence in granules, CTLA-4 and Env are recruited concomitantly to the cell surface (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…It is also possible that HIV-specific cells are present, but they are unresponsive. HIV-specific cells could be unresponsive due to specific tolerance to HIV Ags or to a global unresponsiveness as a consequence of HIV infection, e.g., through cytokine dysregulation (23)(24)(25), cell surface molecule modulation (26), or other mechanisms. HIV Ags coming into contact with CD4 ϩ T cells in the absence of the appropriate costimulatory molecules or the proper cytokine milieu could induce unresponsiveness in HIV-specific CD4 ϩ T cells (27)(28)(29).…”
Section: H Ighly Active Antiretroviral Therapy (Haart)mentioning
confidence: 99%
“…We also attempted to evaluate CD40L and CTLA-4 on the CD8 ϩ cells in these studies, but results demonstrated little to no expression. This may be a function of the cellular phenotype where CD40L and CTLA-4 are expressed more on CD4 ϩ than on CD8 ϩ T cells (26), which was confirmed by analyzing PHA-activated PBLs. The costimulatory molecule CD28 is also a useful marker for activation, but similar to CD40L and CTLA-4 in tissue, the CD8 ϩ cells had little to no detectable expression of CD28.…”
Section: Discussionmentioning
confidence: 62%